PS-BPR02-2: ECULIZUMAB FOR RESCUE OF THROMBOTIC MICROANGIOPATHY IN MALIGNANT HYPERTENSION ASSOCIATED WITH MCTD. (January 2023) - Date, Ryosuke; Kajiwara, Kengo; Johno, Takamitsu; Ko, Takehiro; Nakamura, Tomofumi; Tomita, Masao; Mizumoto, Teruhiko; Kakizoe, Yutaka; Izumi, Yuichiro; Kuwabara, Takashige; Adachi, Masataka; Mukoyama, Masashi
Abstract : Introduction: Eculizumab is effective in atypical hemolytic uremic syndrome (aHUS) caused by complement abnormalities, but its effect on secondary thrombotic microangiopathy (TMA) is obscure. We here report a case of TMA associated with malignant hypertension, who was successfully treated with an ACE inhibitor, plasma exchange and eculizumab. Case report: The patient was a 40-year-old woman presenting with severe blood pressure elevation (BP 240/140 mmHg), nausea, fatigue, headache, and visual disturbances. She had a history of systematic lupus erythematosus (SLE) and had been stable by the treatment with 5 mg/day of prednisolone and 2 mg/day of tacrolimus for a long period. This time, she exhibited Raynaud's phenomenon, mild skin lesions, and heliotrope eruption on the eyelids, together with positive anti-U1-RNP antibodies. She was diagnosed with mixed connective tissue disease (MCTD), instead of SLE. Acute kidney injury (serum creatinine, 3.24 mg/dL), anemia (hemoglobin, 8.8 g/dL) and thrombocytopenia (platelets, 137, 000/μL) were observed. LDH was elevated at 780 IU/L. The haptoglobin level was decreased to less than detection sensitivity and schistocytes were observed in her peripheral blood. The plasma renin activity was beyond the highest limit. On head MRI, posterior reversible encephalopathy syndrome (PRES) was suggested. A renal biopsy was performed, and a histological diagnosis of malignant hypertensive arteriolosclerosis was obtained. Based on these findings, she was diagnosed as accelerated malignant hypertension, possibly due to TMA with a background of MCTD. She was initially treated with nicardipine, enalapril and aliskiren, but this treatment failed to ameliorate the progression of kidney injury and TMA. Therefore, plasma exchange therapy was performed three days in a row, and then hemodialysis and administration of eculizumab were introduced. After weekly induction dose (900 mg once a week) was given four times, administration of 900–1200 mg of eculizumab every 2 weeks were continued. As the treatment was continued, her renal function was improved gradually. Fifteen months after her onset of AKI and TMA, the patient was withdrawn from dialysis and eculizumab therapy. Conclusion: A body of evidence is growing that activation of the complement system may be involved in scleroderma renal crisis. However, the efficacy of eculizumab in TMA, except for aHUS, remains controversial. Our case suggest a possible efficacy of eculizumab along with plasma exchange, as the treatment of malignant hypertension due to scleroderma that was caused by MCTD.